Influence Of Net Income And Current Ratio To Cash Dividends In Mining Companies Listed In Indonesia Stock Exchange Period 2012-2016 - Yulio, Fakhri Harpin; Rina Asmeri (Dinasti Publisher, 2021)
This study aims to determine whether net income and current ratio significantly influence cash dividends in mining companies listed in the Indonesia Stock Exchange period 2012-2016 either partially or simultaneously. The type of data used in this study is quantitative data sourced from the company's financial statements. Data source in this research is secondary data. The population in this study is a manufacturing company coal mining of industrial sub sector listed in the Indonesia Stock Exchange amounted to 24 companies. The sampling technique used purposive sampling technique according to predetermined criteria. Based on predetermined criteria, there are 6 companies. The method of analysis used in this study is multiple linear regression analysis and hypothesis testing using t test and f test. The results of this study indicate that partially net income and current ratio significant effect on cash dividends. Simultaneously net income and current ratio have a significant effect on cash dividends.